(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article is devoted to the improvement of the method of complex treatment with Bepanten ointment for chronic generalized periodontitis accompanied by cardiovascular diseases. The results of the study and analysis of the state of the oral cavity and the main dental indicators are presented in the aspect of comparing patients treated with this complex method of treatment and patients treated with traditional methods of treatment.